AKIBAT HUKUM DAN KEKABURAN NORMA DALAM PENGATURAN UNDANG-UNDANG TENTANG TANGGUNG JAWAB SOSIAL PERSEROAN TERBATAS - Harjono, Dhaniswara K. (Veritas et Justitia, 2022)
Limited Liability Companies in Indonesia, under the applicable law (Law 40/2007 and PP 47/2021), are under the obligation to realize its corporate social responsibility. The idea of CSR is to force the company to make it presence felt beneficially by the local community and wider society.  Unfortunately, not all companies are willing and able to meet its corporate social responsibility, or even if they chose to do so, proportionality is disregard. This paper, using Rudolph von Jhering's point of view, explores and identifies what legal or non-legal factors hinders the implementation of CSR.